Money, mentoring and making friends: The impact of a multidimensional access program on student performance - Kevin Denny; Orla Doyle; Patricia O'Reilly; Vincent O'Sullivan (Institute for Fiscal Studies (IFS), 2010)
There is a well established socioeconomic gradient in educational attainment, despite much effort in recent decades to address this inequality. This study evaluates a university access program that provides financial, academic and social support to low socioeconomic status (SES) students using a natural experiment which exploits the time variation in the expansion of the program across schools. The program has parallels with US affirmative actions programs, although preferential treatment is based on SES rather than ethnicity. Evaluating the effectiveness of programs targeting disadvantaged students in Ireland is particularly salient given the high rate of return to education and the lack of intergenerational mobility in educational attainment. Overall, we identify positive treatment effects on first year exam performance, progression to second year and final year graduation rates, with the impact often stronger for higher ability students. We find similar patterns of results for students that entered through the regular system and the 'affirmative action' group i.e. the students that entered with lower high school grades. The program affects the performance of both male and female students, albeit in different ways. This study suggests that access programs can be an effective means of improving academic outcomes for socio-economically disadvantaged students.
Keywords: I21; 330; Education inequality; Access programs; Natural experiment; Economics of education; Bildungschancen; Studierende; Hochschulpolitik; Bildungsökonomik; Irland